Desenvolvimento e organização empresarial sustentável: responsabilidade legal e o impacto do consumo consciente - Andrade, Dostoievsky Ernesto de Melo (2017)
The expansion of the socio-environmental crisis shows the need for a paradigm shift involving new knowledge, practices and the conjuncture to reconcile its vectors on development goals in accordance with the principles that rule sustainability. Indeed, the notion of sustainability extends its spectrum to dimensions that involve protection of the environment, the economy itself and social protection. Business organizations make a significant contribution to achieving development goals. In this sense, Law with the instruments of command and control and guiding principles that impel the balance and social justice starts to promote the construction of sustainability as an element of the culture envisioning a sustainable future. The present cientific research focuses on the participation of companies in the promotion of a management politics that adopts the premises of environmental rationality and social responsibility, the legal contribution in the impulse to accept this model and the role of the conscious consumer as the center of a movement that seeks to reorder the structure of productive processes in order to overcome the socioenvironmental crisis and thus equalize the patterns of economic progress in building a sustainable identity. The methodology used for this study is based on the hypotheticaldeductive, dialectical method. It is a bibliographical and descriptive research, using the articulation of theoretical frameworks gathered in the interpretations praised by the doctrine, articles, periodicals, and electronic scientific journals. The research reveals that the sustainable model employed by organizations are moved by social and legal pressures, however these actions are more related to the need to impose themselves in the competitive market due to the greater social recognition of the companies that have the mission to contribute with the sustainable development and cultural and collective consciousness changes mainly in the scope of conscious consumption. It is concluded that the sustainable ideal requires that a complex network of dimensions in the economic, environmental, political, scientific and cultural fields must combat the harmful effects of the socioenvironmental crisis, with a decisive reinforcement of responsible corporate management in partnership with public development politics of the state, with the law increasing sanctions and society, changing their consumption patterns.